STRATEGIC EVALUATION OF INVESTMENT CRITERIA THROUGH THE EYES OF A FOREIGN INVESTOR AND NECESSARY TACTICS OF UKRAINIAN FOREST PRODUCTS INDUSTRY TOWARD INVESTMENT ATTRACTIVENESS - Hogaboam, Liliya (Forestry, Forest, Paper and Woodworking Industry, 2024)
Some of the main actions that Ukraine needs to take in order to attract good forest investors are: establishment of attractive laws and regulations, have a design/management framework targeted specifically for foreign investments that is well understood at home and abroad, advertize those opportunities through various suitable media sources, emphasize eco-friendly and green-oriented investment environment, encourage industry tours for key players in the industry of foreign countries and worldwide, comply with various certification standards and world-wide industry agreements, demonstrate technological and intellectual advances in evaluation and logistics.